Desire paths - Lee, Vanessa Jia Xian (Nanyang Technological University, 2025)
In a pragmatic society that prizes material success, many give up on their dreams in favour of stability. Desire Paths follows 3 individuals who choose to defy the norm and chart their own path. From 555 Beatbox, a collective striving to grow an underground art form, to Hidden Heritage, a couple-led initiative uncovering forgotten spaces, and finally, Sam Lo, a muralist whose career began with an act of rebellion — the film unpacks the realities of pursuing one's passions in Singapore.